Innovative Marketing Strategies For MSMEs : Lessons From Successful Cases - Putri Ayu Rahmawati; Lulu Afifah; Cindy Theresia (BADAN PENERBIT STIEPARI PRESS, 2021)
This research paper explores innovative marketing strategies employed by Micro, Small and Medium Enterprises (MSMEs), drawing insights from successful cases. With MSMEs constituting a significant portion of global economic activity, understanding their marketing approaches is vital. Through a comprehensive review of literature and analysis of real-world cases, this study identifies key strategies that have propelled MSMEs to success in competitive markets. These strategies encompass digital marketing, social media engagement, experiential marketing, and strategic partnerships, among others. By examining the experiences of thriving MSMEs, this paper offers valuable insights for practitioners and policymakers aiming to foster growth and competitiveness within the MSME sector. Understanding and implementing innovative marketing strategies can empowerMSMEs to navigate challenges, reach broader audiences, and capitalize on emerging opportunities in today's dynamic business landscape.